2020
DOI: 10.3390/ijms21165888
|View full text |Cite
|
Sign up to set email alerts
|

History of Nonalcoholic Fatty Liver Disease

Abstract: Based on the assumption that characterizing the history of a disease will help in improving practice while offering a clue to research, this article aims at reviewing the history of nonalcoholic fatty liver disease (NAFLD) in adults and children. To this end, we address the history of NAFLD histopathology, which begins in 1980 with Ludwig’s seminal studies, although previous studies date back to the 19th century. Moreover, the principal milestones in the definition of genetic NAFLD are summarized. Next, a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 205 publications
(276 reference statements)
2
92
1
1
Order By: Relevance
“…The prevalence of NAFLD was especially high when schizophrenia comorbid with diabetes (41.33%). Our result was consistent with the previous studies, which showed that diabetes and other metabolic dysfunction were risk factors of NAFLD [ 11 , 12 ]. The association of NAFLD with metabolic syndrome was mutual and bi-directional [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The prevalence of NAFLD was especially high when schizophrenia comorbid with diabetes (41.33%). Our result was consistent with the previous studies, which showed that diabetes and other metabolic dysfunction were risk factors of NAFLD [ 11 , 12 ]. The association of NAFLD with metabolic syndrome was mutual and bi-directional [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our result was consistent with the previous studies, which showed that diabetes and other metabolic dysfunction were risk factors of NAFLD [ 11 , 12 ]. The association of NAFLD with metabolic syndrome was mutual and bi-directional [ 12 ]. Recent study demonstrated that NAFLD was an early predictor of metabolic dysfunction, even in healthy populations without metabolic dysfunction [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…NAFLD, comprising the whole gamut of alcohol-like liver lesions (i.e., steatosis, steatohepatitis with/without fibrosis, cirrhosis and hepatocellular carcinoma (HCC)) though observed in the nonalcoholic [ 14 ], was formerly believed to be “the hepatic manifestation of the Metabolic Syndrome”. However, this old notion is, at best, incomplete and accumulating data strongly indicate that the association of NAFLD with Metabolic Syndrome is indeed mutual and bi-directional [ 15 , 16 , 17 ].…”
Section: Nafld Diagnosis Pitfalls and Classificationmentioning
confidence: 99%
“…As alluded to above, a consistent body of evidence supports the notion that a bi-directional relationship links NAFLD with (features of) Metabolic Syndrome, with insulin resistance being the shared common pathophysiological denominator [ 48 ]. In the medical literature, the historical “chicken and egg” debate regarding the chronological association of NAFLD with Metabolic Syndrome, [ 41 ] eventually found its answer through novel data showing that NAFLD is both the cause and the effect of the Metabolic Syndrome (reviewed in [ 16 , 17 ]). However, it soon became clear that addressing the key pathogenic determinants of NASH would not necessarily improve disease outcomes.…”
Section: Nafld and The Metabolic Syndrome: Chicken Or Egg?mentioning
confidence: 99%